Comparison of Using Conventional Estimating and Sketchup Pro for Bill Quantity Takeoff Process - Diandra, Nadia; Ceisya, Daffira; Farid, Farid (Universitas Batanghari Jambi, 2024)
Departing from academic anxiety that the construction industry in Indonesia has made rapid progress with the adoption of computing technology and methods in recent years. Increasing infrastructure development encourages construction actors to effectively and efficiently improve project quality. However, the role of the quantity surveyor becomes crucial in facing challenges such as manual quantity picking which is prone to errors and cost estimation that is difficult to do based on rough schematic design. In the context of traditional construction projects, quantity lists are arranged based on 2D drawings, but the use of 3D models has diminished since the adoption of BIM. Sketchup, as a 3D modeling software, and its extension Quantifier Pro provide a solution by combining 3D models to produce accurate quantity takeoff calculations on the Bill of Quantity. This research aims to develop methods to improve the quantity accuracy of elements of an incomplete or incorrect Sketchup model, in the hope of reducing modeling time, improving quantity retrieval performance, and making Sketchup-based cost estimation more effective and efficient in the context of construction. This research method involves 3D modeling using the Sketchup Pro application, using secondary data in the form of Detailed Engineering Design (DED) working drawings. Volume calculation in the Bill of Quantity is done with the help of Sketchup Pro software. The research location is in the Mullberry Cluster residential project, Bekasi City, West Java. The house building in this project was chosen as an object of comparison between conventional calculation methods and calculation methods using Sketchup Pro software. The main focus is to overcome the challenges of manual quantity picking and cost estimation from rough schematic design, emphasizing the crucial role of quantity surveyors. The results showed that the use of 3D models in Sketchup can increase the accuracy of cost estimation and reduce modeling time. The conclusion of the study confirms that Sketchup as an effective alternative solution in increasing efficiency and accuracy in the construction process, especially in the context of taking the quantity of architectural work elements, contributes positively to the development of more sophisticated cost estimation methods in the Indonesian construction industry.